2021
DOI: 10.1037/cdp0000416
|View full text |Cite
|
Sign up to set email alerts
|

“I am affected in all the ways … ”: A phenomenographic analysis of Latinx adolescents’ perceptions of family separations at the border.

Abstract: Objectives: This phenomenographic analysis examines how news of family separations at the U.S.-Mexico border shaped variations of experience and perceptions among U.S. Latinx adolescents across parental residency status. Method: In 2018-2019, 340 15-18-year-old Latinx adolescents in the Washington D.C. area participated in a study on immigration actions and responded to an open-ended question detailing how news of family separations at the border affected them and their families. The sample was comprised of eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Incidents such as the separations at the border and certainly the shooting in El Paso—a border town—may have been more poignant for these participants than for Latinx young adults in other locations. With that being said, another study (e.g., Jordan et al, 2021) found that Latinx adolescents deeply internalized the pain of families separated at the border in 2018 despite living nearly 2,000 miles away.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Incidents such as the separations at the border and certainly the shooting in El Paso—a border town—may have been more poignant for these participants than for Latinx young adults in other locations. With that being said, another study (e.g., Jordan et al, 2021) found that Latinx adolescents deeply internalized the pain of families separated at the border in 2018 despite living nearly 2,000 miles away.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the participant in Theme 1 (proximal witnessing) who described witnessing his parents work difficult jobs with long hours did not mention the experience of feeling alone as a child or anything related to his own privation; rather, he focused on how painful it was to watch his parents go through hardship, indicating an experience that is inherently vicarious and empathy based. Only this study and a few select others have explored specifically the experience of bearing witness to an event and the effects of such witnessing among Latinx communities (e.g., N. Heard-Garris et al, 2021;Jordan et al, 2021). The work that has been done documenting the experience of witnessing has included Black persons witnessing the beating of Rodney King (Alexander, 1994) and Jewish persons witnessing depictions of the Holocaust (Keats, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature to this point has explored the consequences of witnessing violence and police brutality against Black people in the United States (Alexander, 1994). To our knowledge, only one other study has specifically documented similar effects of vicarious witnessing within Latinx adolescents who observed family separations at the border in 2018 through the media (Jordan et al, 2021). More research is needed to parse out how "spillover effects" (Aranda et al, 2014) or a "culture of fear" (Vargas et al, 2017) may be similar or different from vicarious witnessing, such as in a study of Latina mothers which found that birth outcomes were affected following a local ICE raid (Novak et al, 2017).…”
Section: Adolescents With Permanent Resident and Citizen Parentsmentioning
confidence: 99%